1994
DOI: 10.1002/bjs.1800811014
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of reflux in recurrent varicose veins assessed by duplex scanning

Abstract: 5 Scott DJA, Vowden P, Beard JD, Horrocks M. Non-invasive estimation of peripheral resistance using pulse generated runoff heforefemorodistal bypass. BrJSurg 1990; 77: 391-5. 6 Beard JD, Scott DJA, Evans JM, Skidmore R, Horrocks M. Pulse-generated run-off: a new method of determining calf vessel patency. Br J Surg 1988; 75: 36 1-3. 7 Roedersheimer LR, Feins R, Green RM. Doppler evaluation of thepedalarch.AmJSurg 1981;142:601-4. 8 Altman DG. Pmctical Statistics for Medical Research. London: Chapmanand Hall, 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 5 publications
0
15
0
1
Order By: Relevance
“…Pathological reflux was defined as reversal of the colour Doppler signal and the pulsed Doppler signal for more than 0.5 s after a manual calf squeeze [19][20][21].…”
Section: Assessment Of the Effectiveness Of The Sfj Ligationmentioning
confidence: 99%
“…Pathological reflux was defined as reversal of the colour Doppler signal and the pulsed Doppler signal for more than 0.5 s after a manual calf squeeze [19][20][21].…”
Section: Assessment Of the Effectiveness Of The Sfj Ligationmentioning
confidence: 99%
“…confirm that 20% of recurrences occur in the first year, using the same diagnostic param­eters 11 . These results have been confirmed by Redwood and Lambert, with 58% having some form of residual SFJ incompetence after stripping 12 . Sheppard has shown that 90% of 204 recurrent limbs were associated with neovascularization 13 and these findings have been reiterated by Glass 14 .…”
Section: Discussionmentioning
confidence: 70%
“…I). The most common source of recurrence following surgery of the long saphenous system is the sapheno-femoral junction (Figs 2,3) [18][19][20]. However, this only accounts for 40% of new varices, and reliable investigation is necessary to determine whether veins fill from other sources.…”
Section: Assessment Of Patients With Recurrent Varicose Veinsmentioning
confidence: 99%